Evolutionary Change in Locomotion Close to the Origin of Amniotes Inferred From Trackway Data in an Ancestral State Reconstruction Approach - Buchwitz, Michael; Jansen, Maren; Renaudie, Johan; Marchetti, Lorenzo; Voigt, Sebastian (Frontiers in Ecology and Evolution, 2021)
Among amniote and non-amniote tetrapod trackways from late Carboniferous to early Permian deposits, certain trackway measures vary notably. Some of this variability can be attributed to evolutionary changes in trackmaker anatomy and locomotion style close to the origin of amniotes. Here we demonstrate that steps in early amniote locomotion evolution can be addressed by applying methods of ancestral state reconstruction on trackway data – a novel approach in tetrapod ichnology. Based on (a) measurements of 186 trackways referred to the Carboniferous and early Permian ichnogenera Batrachichnus, Limnopus, Hylopus, Amphisauropus, Matthewichnus, Ichniotherium, Dimetropus, Tambachichnium, Erpetopus, Varanopus, Hyloidichnus, Notalacerta and Dromopus, (b) correlation of these ichnotaxa with specific groups of amphibian, reptiliomorph, synapsid and reptilian trackmakers based on imprint morphology and (c) known skeletal-morphology-based phylogenies of the supposed trackmakers, we infer ancestral states for functionally controlled trackway measures in a maximum likelihood approach. The most notable finding of our analysis is a concordant change in trackway parameters within a series of ancestral amniote trackmakers, which reflects an evolutionary change in locomotion: In the ancestors of amniotes and diadectomorphs, an increase in body size was accompanied by a decrease in (normalized) gauge width and glenoacetabular length and by a change in imprint orientation towards a more trackway-parallel and forward-pointing condition. In the subsequent evolution of diadectomorph, synapsid and reptilian trackmakers after the initial diversification of the clades Cotylosauria and Amniota, stride length increased whereas gauges decreased further or remained relatively narrow within most lineages. In accordance with this conspicuous pattern of evolutionary change in trackway measures, we interpret the body size increase as an underlying factor that triggered the reorganization of the locomotion apparatus. The secondary increase in stride length, which occurred convergently within distinct groups, is interpreted as an increase in locomotion capability when the benefits of reorganization came into effect. The track-trackmaker pair of Ichniotherium sphaerodactylum and Orobates pabsti from the early Permian Bromacker locality of the Thuringian Forest fits well with the modelled last common ancestor of amniotes – with the caveat that the Bromacker material is younger and some of the similarities appear to be due to convergence.